‘‘The provocation is titillating.’’ Sven Wernström in Iceland - Holownia, Olga (Barnboken, 2012)
The article discusses the reception and impact of Sven Wernström’s views and works in Iceland. In particular, it retraces the controversy which surrounded the 1978 translation of his book Kamrat Jesus (1971) and recounts the heated debate over the book which took place both in the press and in the Icelandic parliament. Wernström’s prose and critical voice is also considered within the context of the so-called social realist movement in Icelandic literature for children and young adults.Keywords: Icelandic translations; reception; social realism; neorealism; Icelandic children’s literature; Þórarinn Eldjárn; controversial books(Published: 28 November 2012)Citation: Barnboken - tidskrift för barnlitteraturforskning/Journal of Children’s Literature Research, Vol. 35, 2012 http://dx.doi.org/10.3402/clr.v35i0.19990